ENVIRONMENTAL FACTORS AND INVOLVEMENT OF WOMEN IN ENTREPRENEURSHIP THROUGH SELF-LEADERSHIP BEHAVIOR - Rimsha Khalid, Waqas Ali, Shahid Mahmood, Dr. Imran Ibrahim Alasan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The aims of this study to examine that factors which influence to women entrepreneurs in business activities. These factors are included work-family interference, cultural and social support and entrepreneurial skill. Further, this study to investigate the mediating effect of self-leadership between work-family interference, cultural and social support and entrepreneurial skill on the participation of women in entrepreneurial activities. Structure questionnaire used in this study for the data collection from women entrepreneurs in Pakistan. There were 384 questionnaires distributed, and approximately 347 response were collected after omitted of 17 questionnaires which were not suitable filled or greater than 5% missing values. The response rate was 90.36%. Smart PLS software used in this study for data analysis. The study findings are indicated that the positive relation between work-family interference, cultural and social support and entrepreneurial skill on the participation of women in entrepreneurial activities. Moreover, this study also indicated that the significant relationship between all factors which influence the participation of women in entrepreneurial activities with the mediating effect of a self-leadership role. The study recommended that policymakers should make the policies for women entrepreneurs that would be effect toward self-leading behavior in business activities. It contributes to understanding the factors for women in development in business. Further, it also recommends that the use of this study in academic level and also encourage the women in developing the motivational factors towards entrepreneurship.